Quality of life and its associated factors among patients with COPD before and after an exacerbation in Sri Lanka - Buddhika mahesh; Wasantha Gunathunga; Saroj Jayasinghe; Mahendra Arnold; Vajira Croos; Sinha de Silva (College of Community Physicians of Sri Lanka, 2018)
Abstract Purpose: This study was done to describe quality of life (QOL) and its associated factors among patients with Chronic Obstructive Pulmonary Disease (COPD) before and after an exacerbation in the premier province of Sri Lanka, which is a lower middle income country. Methods: Longitudinal study with two waves of data collection was done in 13 government hospitals among 289 participants in 2015. Sample size was calculated using a formula for estimating QOL in numerical scale with reference to documented global literature. The study population included admitted patients with an exacerbation of COPD. The pre-exacerbation and the post-discharge one month quality of life were assessed using SF-36 generic QOL tool. Bivariate analysis was followed by multivariate analysis. Results: For seven QOL domains there was a significant decline in QOL at one month post-discharge (p<0.05) compared to pre-exacerbation figures. Age (two domains) income (seven domains) and health infrastructure (seven domains) significantly associated with the pre-exacerbation QOL. Pre-exacerbation QOL significantly correlated with post-discharge QOL for five domains. A higher-age, higher monthly income, better health-infrastructure and a lower severity of the exacerbation were independent predictors of a lowered QOL following an exacerbation. Conclusions: Younger age, higher income and better health-infrastructure are associated with higher baseline QOL of COPD patients. The baseline QOL scores are worsened following an exacerbation. Post-discharge QOL can be predicted with pre-exacerbation QOL for five domains of QOL. Older age, higher income level, better level of health infrastructure and lower severity of the exacerbation are associated with a reduction of the pre-exacerbation QOL at 1one month from the hospital discharge. Key Words: COPD, Quality of life, Exacerbation, Sri Lanka, SF-36, Chronic Respiratory Disease, Chronic Obstructive Pulmonary Disease